Clinical Effectiveness and Safety of Antivirals for Influenza in Pregnancy - Chow, Eric J (Open Forum Infect Dis, 2021)
Seasonal influenza epidemics result in substantial health care burden annually. Early initiation of antiviral treatment of influenza has been shown to reduce the risk of complications and duration of illness. Pregnant and postpartum women may be at increased risk for influenza-associated complications; however, pregnant women have been generally excluded from clinical trials of antiviral treatment of influenza. In this review, we summarize the available evidence on the clinical effectiveness and safety of antiviral treatment of pregnant women with influenza. Observational data show a reduction of severe outcomes when pregnant and postpartum women are treated with oseltamivir and other neuraminidase inhibitors without increased risk of adverse maternal, fetal, or neonatal outcomes. Due to lack of safety and efficacy data for baloxavir treatment of pregnant and postpartum women, baloxavir is currently not recommended for use in these populations.